Douro demarcated region´s institutions: a contribution to its study - ALBUQUERQUE, Ana Silvia (Revista Jurídica Portucalense, 2022)
Established by Royal Charter on the 10th September 1756, the “Companhia Geral da Agricultura das Vinhas do Alto Douro” creates the first demarcated region of wine production regulated in the whole world. This institution is part of Pombal´s mercantilist policy fostering Portugal´s economic and commercial reorganization based on several monopolist and privileged companies. Specifically, the Company is a response to problems related to the declining quality of Douro wines from 1750. It went through several organizational stages, according to the political and economic situation. Nowadays, the importance of Douro wines quality is reaffirmed and its regional identity is preserved under IVDP supervision.